Malaysia Technology Expo 2021 MTE Awards - Nabilah Filzah, Mohd Radzuan (Faculty of Computing, 2021)
PEKAN, 30 August 2021 - Congratulations to Associate Professor Ts. Dr. Mazlina Abdul Majid from FK,UMP for winning Gold Medal and Special Awards in the MTE 2021 for the innovation of PISAH application.